2022
DOI: 10.1128/spectrum.01998-22
|View full text |Cite|
|
Sign up to set email alerts
|

Direct Nasal Swab for Rapid Test and Saliva as an Alternative Biological Sample for RT-PCR in COVID-19 Diagnosis

Abstract: There are several methods for the diagnosis of coronavirus disease 2019 (COVID-19), and the choice of methods depends mostly on the resources and level of sensitivity required by the user and health care providers. Still, reverse transcription polymerase chain reaction (RT-PCR) has been chosen as the best method using direct naso-oropharyngeal swabs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…For these reasons, in addition to examining nasopharyngeal samples, saliva, and urine samples were also used in this study. In the present study, the sensitivity of SARS-CoV-2 detection in saliva and nasopharynx samples was reported as 88.2% and 92.9%, respectively, the results were consistent with the results of Sazed et al [ 40 ]. Based on the obtained results in the current study, the RT-LAMP method can identify the virus carriers, if the RT-qPCR method proves otherwise.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…For these reasons, in addition to examining nasopharyngeal samples, saliva, and urine samples were also used in this study. In the present study, the sensitivity of SARS-CoV-2 detection in saliva and nasopharynx samples was reported as 88.2% and 92.9%, respectively, the results were consistent with the results of Sazed et al [ 40 ]. Based on the obtained results in the current study, the RT-LAMP method can identify the virus carriers, if the RT-qPCR method proves otherwise.…”
Section: Discussionsupporting
confidence: 93%
“…However, RT-qPCR may fail to detect the virus and produce false-negative results, particularly if the viral load is very low in the patient’s sample. This can occur in patients who have recently been infected, or in patients who are in the early stages of the disease [ 22 , 40 ]. As in the current study, in the investigation of 55 asymptomatic people suspected of SARS-CoV-2 infection, all 55 cases were negative in the repeat RT-qPCR test after 48 h. However, in the repeat RT-LAMP test, 6 out of 55 people tested positive and still had no symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…A notable advantage of the detection of COVID-19 through RT-PCR of saliva is that it reduces the chances of spreading SARS-CoV-2. A study evaluated saliva and NP samples, and the sensitivity was found to be 85.2% for saliva and 94.5% for NP [ 42 ]. Another study has reported the presence of SARS-CoV-2 in the nasal vestibule and the sensitivity of testing this particular specimen for diagnosis of SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the specificity was as high as ≥95%. Additionally, the CareStart TM COVID-19 Antigen Home Test was reported to be able to detect patients with different variants of SARS-CoV-2 [ 52 ].…”
Section: Antigen Tests Amid the Battle Against Sars-cov-2 In Koreamentioning
confidence: 99%